The Effectiveness of EFL Students’ Use of ICT on Developing their Autonomy - Said Oussou (The Journal of Studies in Language, Culture and Society, 2024)
Learner autonomy has received its due amount of attention in the literature of foreign language teaching. The concept has come to life since the 1980s. Learner autonomy has been considered as a goal of education, which ICTs, when used appropriately, may help in fostering. As such, the present study has continued that very focus by investigating the degree of autonomy that Moulay Ismail University EFL students enjoy and the extent to which they use ICTs for their learning. In essence, the study aimed at investigating how ICT’s use and learner autonomy are related. A cross-sectional quantitative design underpinned the study. A self-completion questionnaire was thus employed as an instrument to collect the data. As such, a total of 109 EFL undergraduate students took part in the study. A questionnaire was administered to the respondents to find out their level of use of ICT as well as their level of autonomy. Findings revealed that the students used ICT to a large extent, and their level of autonomy was shown to be high. It was, thus, found that their use of ICT level and autonomy were significantly related.